1991
DOI: 10.1111/j.1365-2265.1991.tb01735.x
|View full text |Cite
|
Sign up to set email alerts
|

Corticotrophin releasing hormone (CRH1–41) stimulates the secretion of adrenocorticotrophin, vasopressin and oxytocin but not adrenocorticotrophin precursors: evidence from petrosal sinus sampling in man

Abstract: To examine the relationship between corticotrophin releasing hormone (CRH), arginine vasopressin (AVP) and oxytocin (OXT) we have studied the responses of adenohypophyseal and neurohypophyseal hormones to CRH in eight patients (age 26-64 years, six female) with suspected pituitary-dependent Cushing's syndrome during bilateral, simultaneous inferior petrosal sinus catheterization. Blood samples were taken from both petrosal sinuses and a peripheral vein before, and at 5-min intervals for 15 min after, an intrav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

1993
1993
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 18 publications
2
12
0
1
Order By: Relevance
“…This data is in agreement with a previous reported evalu ating the a-MSH response to CRH in the peripheral blood [26]. Similarly, Nussey et al [40] were unable to find any change of ACTH precursors during CRH stimulation in the inferior petrosal sinuses. It should be considered, how ever, that in the above-mentioned paper [40] a small series of patients, namely 8, with Cushing's disease are studied.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This data is in agreement with a previous reported evalu ating the a-MSH response to CRH in the peripheral blood [26]. Similarly, Nussey et al [40] were unable to find any change of ACTH precursors during CRH stimulation in the inferior petrosal sinuses. It should be considered, how ever, that in the above-mentioned paper [40] a small series of patients, namely 8, with Cushing's disease are studied.…”
Section: Discussionsupporting
confidence: 81%
“…Similarly, Nussey et al [40] were unable to find any change of ACTH precursors during CRH stimulation in the inferior petrosal sinuses. It should be considered, how ever, that in the above-mentioned paper [40] a small series of patients, namely 8, with Cushing's disease are studied. Because in our series only 23.3% of the patients had a significant increase of a-MSH during CRH chal lenge, it is quite possible that when a small number of cases is studied, this finding may go unnoticed.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, Nussey et al reported lateralized AVP and OT secretion into the IPS of patients with Cushing disease after administration of CRH, without a concomitant change in peripheral AVP or OT levels (31). However, this finding could have been caused by the presence of the pituitary adenoma and might not have represented normal physiology.…”
Section: Introductionmentioning
confidence: 65%
“…Nussey et al (1991) measured both hormones in the inferior petrosal sinus and peripheral venous samples following CRH administration in six women and two men with suspected Cushing's syndrome. AVP and ACTH were both increased in the first 5-min petrosal sinus sample, after which AVP declined and ACTH continued to increase.…”
Section: Discussionmentioning
confidence: 99%